# Calculator search results

Formula
$$x ^ { 2 } - 6 x + 8 = 0$$
$\begin{array} {l} x = 4 \\ x = 2 \end{array}$
Solve quadratic equations using the square root
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 6 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 8 } = \color{#FF6800}{ 0 }$
 Convert the quadratic expression on the left side to a perfect square format 
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 8 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( x - 3 \right ) ^ { 2 } \color{#FF6800}{ + } \color{#FF6800}{ 8 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } ^ { \color{#FF6800}{ 2 } } = 0$
 Move the constant to the right side and change the sign 
$\left ( x - 3 \right ) ^ { 2 } = \color{#FF6800}{ - } \color{#FF6800}{ 8 } \color{#FF6800}{ + } \color{#FF6800}{ 3 } ^ { \color{#FF6800}{ 2 } }$
$\left ( x - 3 \right ) ^ { 2 } = - 8 + \color{#FF6800}{ 3 } ^ { \color{#FF6800}{ 2 } }$
 Calculate power 
$\left ( x - 3 \right ) ^ { 2 } = - 8 + \color{#FF6800}{ 9 }$
$\left ( x - 3 \right ) ^ { 2 } = \color{#FF6800}{ - } \color{#FF6800}{ 8 } \color{#FF6800}{ + } \color{#FF6800}{ 9 }$
 Add $- 8$ and $9$
$\left ( x - 3 \right ) ^ { 2 } = \color{#FF6800}{ 1 }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 1 }$
 Solve quadratic equations using the square root 
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } = \pm \sqrt{ \color{#FF6800}{ 1 } }$
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } = \pm \sqrt{ \color{#FF6800}{ 1 } }$
 Solve a solution to $x$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ 3 }$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ 3 }$
 Separate the answer 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 3 } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ 3 } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \\ x = 3 - 1 \end{array}$
 Add $3$ and $1$
$\begin{array} {l} x = \color{#FF6800}{ 4 } \\ x = 3 - 1 \end{array}$
$\begin{array} {l} x = 4 \\ x = \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \end{array}$
 Subtract $1$ from $3$
$\begin{array} {l} x = 4 \\ x = \color{#FF6800}{ 2 } \end{array}$
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture